COVID-19 Learning Losses : Rebuilding Quality Learning for All in the Middle East and North Africa - UNESCO; UNICEF; World Bank (UNESCO, Paris, UNICEF, New York, and World Bank, Washington, DC, 2021)
Since the beginning of the pandemic, efforts have been made to monitor both school closures (and re-opening) and the measures put in place to ensure continuity of learning. These include the Survey of Ministries of Education on National Responses to COVID-19, jointly supported by UNESCO, UNICEF and the World Bank. However, to date, no systematic evidence has been available on how students’ learning is being affected by the disruptions caused by the pandemic or on the impact of education response measures initiated by governments. This report contributes to filling this evidence gap and includes a series of simulations of potential learning losses due to COVID-19 and exploration of their longer-term implications. The analysis is based on the Enabling learning for all framework, which outlines access, engagement and enabling environment as the three crucial enablers for learning, while the simulation assumptions are informed by the evidence on school closures and governments’ education-related responses, collected through the joint survey.